2012
DOI: 10.1073/pnas.1211364109
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging reveals target-search mechanisms during DNA mismatch repair

Abstract: The ability of proteins to locate specific targets among a vast excess of nonspecific DNA is a fundamental theme in biology. Basic principles governing these search mechanisms remain poorly understood, and no study has provided direct visualization of single proteins searching for and engaging target sites. Here we use the postreplicative mismatch repair proteins MutSα and MutLα as model systems for understanding diffusion-based target searches. Using single-molecule microscopy, we directly visualize MutSα as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
208
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(226 citation statements)
references
References 45 publications
16
208
0
Order By: Relevance
“…In the presence of ADP and ATP, the k on2 were 2.5-and 30-fold faster than the k on for the HsRAD51-bound short synthetic D-loop obtained under identical conditions (Table 1 and Table S3). These results support previous studies that demonstrated that MSH proteins search and then bind to a DNA mismatch through a 2D sliding mechanism (14,(17)(18)(19)(20). Taken as a whole, we conclude that hMSH2-hMSH6 recognizes mismatch within D-loop formed by RAD51 and is capable of forming an ATP-bound sliding clamp.…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butsupporting
confidence: 80%
See 3 more Smart Citations
“…In the presence of ADP and ATP, the k on2 were 2.5-and 30-fold faster than the k on for the HsRAD51-bound short synthetic D-loop obtained under identical conditions (Table 1 and Table S3). These results support previous studies that demonstrated that MSH proteins search and then bind to a DNA mismatch through a 2D sliding mechanism (14,(17)(18)(19)(20). Taken as a whole, we conclude that hMSH2-hMSH6 recognizes mismatch within D-loop formed by RAD51 and is capable of forming an ATP-bound sliding clamp.…”
Section: Hmsh2-hmsh6 Sliding Clamp Is Constrained Within the D-loop Butsupporting
confidence: 80%
“…ATP binding by hMSH2-hMSH6 results in the formation of a sliding clamp that is released from the mismatch and diffuses along the DNA duplex (17,21). In the case of HR intermediates, the ATP-bound hMSH2-hMSH6 sliding clamp is confined within the mismatch-containing D-loop until it comes in contact with displaced ssDNA strand or with the branch points at the end of the D-loop (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, the cellular concentration of HsMSH2-HsMSH6 has been estimated to be ∼250 nM (24). All of the HsMSH2-HsMSH6 proteins appeared to diffuse randomly on the mismatched DNA consistent with ATPbound sliding clamps as described previously (20,(25)(26)(27).…”
Section: Significancementioning
confidence: 99%